Comparing chebyshev polynomials and adomian decomposition method in solving nonlinear volterra integral equations of second kind - Siti Aminah Mohamad Sapawi, 1990- (Johor Bahru, Johor: Universiti Teknologi Malaysia, 2014)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2014